2002
DOI: 10.1113/jphysiol.2001.013230
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain blood flow and cerebral hemispheric oxygen consumption during acute hypoxaemia in the llama fetus

Abstract: Unlike fetal animals of lowland species, the llama fetus does not increase its cerebral blood flow during an episode of acute hypoxaemia. This study tested the hypothesis that the fetal llama brain maintains cerebral hemispheric O2 consumption by increasing cerebral O2 extraction rather than decreasing cerebral oxygen utilisation during acute hypoxaemia. Six llama fetuses were surgically instrumented under general anaesthesia at 217 days of gestation (term ca 350 days) with vascular and amniotic catheters in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Our experiments show that absolute mean brain temperature decreased 0.54°C during prolonged hypoxaemia, indicating lower heat production or an increase in release of heat from the brain. Previous findings show a lowering of brain cortex oxygen consumption in an episode of acute hypoxaemia (1 h) in the llama fetus (Llanos et al 2002), suggesting that a reduction in heat production (beyond the scope of the present study) is probably present during the first hour of hypoxaemia. A reduction in brain heat production has been shown by Hunter et al (2003) in an episode of 30 min hypoxaemia in fetal sheep.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Our experiments show that absolute mean brain temperature decreased 0.54°C during prolonged hypoxaemia, indicating lower heat production or an increase in release of heat from the brain. Previous findings show a lowering of brain cortex oxygen consumption in an episode of acute hypoxaemia (1 h) in the llama fetus (Llanos et al 2002), suggesting that a reduction in heat production (beyond the scope of the present study) is probably present during the first hour of hypoxaemia. A reduction in brain heat production has been shown by Hunter et al (2003) in an episode of 30 min hypoxaemia in fetal sheep.…”
Section: Discussionmentioning
confidence: 47%
“…Remarkably, unlike fetuses of lowland species, the llama fetus responds to acute hypoxaemia with only a minor increase in cerebral blood flow (Llanos et al 2003). Furthermore, the fetal llama shows a progressive fall in brain oxygen delivery and cerebral oxygen consumption with progression of the fetal hypoxaemia (Llanos et al 2002). We have shown that the electrocorticogram flattens under these conditions of hypoxaemia, and seizure activity does not occur, which suggests that no hypoxaemic damage occurs (Llanos et al 2003).…”
mentioning
confidence: 99%
“…Characteristically, the fetal llama has a greater total peripheral vascular resistance than the sheep, both in normoxemia and in hypoxemia (28,34). Furthermore, unlike fetuses of lowland species (34), the fetal llama responds to acute hypoxemia with a marked peripheral vasoconstriction and with little or no increase in cerebral blood flow (13,14,27,29). This response to hypoxemia suggests differences in the gain of chemoreflexes or in the balance between endocrine and autocrine vasoconstrictor and vasodilator mechanisms between fetuses of highland and lowland species.…”
mentioning
confidence: 92%
“…To this effect, here we emphasize that no information is available on the early morphogenesis of the central nervous system (CNS) during the first trimester of pregnancy. Since the alpaca lives in the high altitude hypoxic environment, the species may represent a particularly interesting translational model for the study of the human adaptation to the same environment (Llanos et al, , ; Ebensperger et al, ; Herrera et al, ; Moraga et al, ).…”
mentioning
confidence: 99%